Work-Life Balance, Employee Workload, Leadership Style In Its Influence On Turnover Intention At Bina Insan Foundation - Fadilla Ayu Puspitasari; Maulidyah Amalina Rizqi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to examine the effect of work-life balance, employee workload, and leadership style on  turnover intention in employees at Yayasan Bina Insan. A random sample of 99 employees was used in the multiple linear regression analysis. Questionnaires are used to collect data, which assesses factors such as work-life balance, workload, leadership style, and intention to leave. Leadership style has a smaller but still considerable beneficial effect on turnover intention, while work-life balance and employee workload also have a large positive effect. According to the R² coefficient, the three independent factors account for 67% of the variance in turnover intention. Based on these results, it is recommended that companies improve work-life balance and manage employee workload more effectively, as well as improve supportive leadership styles to reduce turnover rates.